Energy consumption of below-knee amputees during walking; A review of literature - Tahmoureth Tahmasebi; Razieh Tahmasebi (Vesnu Publications, 2014)
Abstract Introduction: Measuring the energy consumption is one of the effective methods for evaluating the effectiveness of the prostheses in lower limb amputees. Every prosthetic components that could reduce the energy consumption while increasing patient comfort, it is the best choice for this group. Therefore, the aim of this study was to evaluate the energy consumption of below-knee amputees and the factors affecting it. Materials and Methods: This review was done with use of these keywords: below knee amputee, trans-tibial amputee, Energy expenditure, Oxygen consumption and walking. An electronic search was done via the PubMed, Cochrane library, Google scholar and ISI web of science databases from 1970 to 2012. Results: 76 articles were obtained after review the titles and abstracts of papers, some of them were excluded due to non-communication purposes. Then 20 articles were eligible and were analyzed and at the end, the conclusion was taken. The scores of reporting, external validity, internal validity (bias), and internal validity (confounding) varied between 4-9, 2-3, 4-5, and 3-5, respectively. Conclusion: This review shows that the energy consumption of below-knee amputees during walking was more than non-amputees persons. It is influenced by many factors including walking speed, level of amputation and alignment. Contrary to popular perception, the evidence shows that the weight of the prosthesis, type of prosthetic feet and length of stamp was no significant effect on energy consumption. The effect of prostheses suspension and proper fitting on energy consumption, the power consumption is not studied. Research conducted by the larger community that includes a variety of below-knee amputation, be required to appear. Keywords: Below knee amputees, Energy consumption, Walking.